The role of the priming loop in influenza A virus RNA synthesis - Te Velthuis, A; Robb, N; Kapanidis, A; Fodor, E (Nature, 2016)
RNA-dependent RNA polymerases (RdRps) are used by RNA viruses to replicate and transcribe their RNA genomes1 . They adopt a closed, right-handed fold with conserved subdomains called palm, fingers and thumb1,2. Conserved RdRp motifs A–F coordinate the viral RNA template, NTPs and magnesium ions to facilitate nucleotide condensation1 . For the initiation of RNA synthesis, most RdRps use either a primer-dependent or de novo mechanism3. The influenza A virus RdRp, in contrast, uses a capped RNA oligonucleotide to initiate transcription, and a combination of terminal and internal de novo initiation for replication4. To understand how the influenza A virus RdRp coordinates these processes, we analysed the function of a thumb subdomain β-hairpin using initiation, elongation and single-molecule Förster resonance energy transfer (sm-FRET) assays. Our data indicate that this β-hairpin is essential for terminal initiation during replication, but not necessary for internal initiation and transcription. Analysis of individual residues in the tip of the β-hairpin shows that PB1 proline 651 is critical for efficient RNA synthesis in vitro and in cell culture. Overall, this work advances our understanding of influenza A virus RNA synthesis and identifies the initiation platform of viral replication.